Exploring diagnostic and therapeutic implications of endoscopic mucosal resection in EUS-staged T2 esophageal adenocarcinoma - Gotink, Annieke W.; Spaander, Manon C. W.; Doukas, Michael; Tang, Thjon J.; Didden, Paul; Wijnhoven, Bas P. L.; Bruno, Marco J.; Koch, Arjun D. (Endoscopy, 2017)
Background and study aims Treatment strategies for clinical (c)T2N0M0 esophageal adenocarcinoma (EAC) are subject to debate owing to the relative inaccuracy of tumor staging by endoscopic ultrasound (EUS), with profound implications in overstaged patients. We aimed to evaluate the final histological diagnosis of patients initially staged as having a cT2 tumor by EUS, and to assess the value of endoscopic reassessment by an interventional endoscopist, followed by an endoscopic resection when deemed feasible. Patients and methods Two distinct cohorts of patients with cT2 EAC as determined by EUS were included: a retrospective surgical cohort of patients treated by primary esophagectomy, and a prospective cohort of patients who underwent an endoscopic reassessment by an interventional endoscopist. The main outcome measure was the final pathological (p)T stage. Results We identified 134 patients with stage T2 EAC from the surgical cohort. In 72 patients treated by primary esophagectomy, 32/72 (44 %) were downstaged to a pT1 tumor. In 12/72 (17 %), the surgical resection specimen showed tumor characteristics that fulfilled the current criteria for a curative endoscopic resection. In 13 prospectively identified patients with cT2N0M0 EAC, an expert endoscopic reassessment was done. In 11/13 (85 %) the lesion appeared endoscopically resectable and a complete endoscopic resection was performed. Histology revealed a pT1 tumor in all 11 patients, with 5/13 (38 %) fulfilling current criteria for a curative endoscopic resection.Conclusions In this study, 44 % of cT2 EACs were in fact pT1 tumors. Curative treatment by endoscopic resection was achieved in more than a third of these cases. To avoid an unnecessary esophagectomy, an endoscopic reassessment by an interventional endoscopist is recommended for all patients with cT2N0M0 EAC.